Study of the Halogen Bonding between Pyridine and Perfluoroalkyl Iodide in Solution Phase Using the Combination of FTIR and 19F NMR. (11th June 2013) - Hawthorne, Briauna; Fan-Hagenstein, Haiyan; Wood, Elizabeth; Smith, Jessica; Hanks, Timothy
Abstract : Halogen bonding between pyridine and heptafluoro-2-iodopropane (iso-C3 F7 I)/heptafluoro-1-iodopropane (1-C3 F7 I) was studied using a combination of FTIR and 19 F NMR. The ring breathing vibration of pyridine underwent a blue shift upon the formation of halogen bonds with both iso-C3 F7 I and 1-C3 F7 I. The magnitudes of the shifts and the equilibrium constants for the halogen-bonded complex formation were found to depend not only on the structure of the halocarbon, but also on the solvent. The halogen bond also affected the C α -F (C-F bond on the center carbon) bending and stretching vibrations in iso-C3 F7 I. These spectroscopic effects show some solvent dependence, but more importantly, they suggest the possibility of intermolecular halogen bonding among iso-C3 F7 I molecules. The systems were also examined by 19 F NMR in various solvents (cyclohexane, hexane, chloroform, acetone, and acetonitrile). NMR dilution experiments support the existence of the intermolecular self-halogen bonding in both iso-C3 F7 I and 1-C3 F7 I. The binding constants for the pyridine/perfluoroalkyl iodide halogen bonding complexes formed in various solvents were obtained through NMR titration experiments. Quantum chemical calculations were used to support the FTIR and 19 F NMR observations.